2008
DOI: 10.2108/zsj.25.875
|View full text |Cite
|
Sign up to set email alerts
|

Spring Migration Routes of Mallards (Anas platyrhynchos) that Winter in Japan, Determined from Satellite Telemetry

Abstract: Wild birds, in particular waterfowl, are common reservoirs of low pathogenic avian influenza viruses, and infected individuals could spread the viruses during migrations. We used satellite telemetry to track the spring migration of the mallard ducks ( Anas platyrhynchos ) that winter in Japan. We studied their migration routes, distribution of stopover and breeding sites, and timing of migration movements. We tracked 23 mallards from four different wintering sites. Nine of the 23 mallards reached presumable br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 32 publications
3
42
0
Order By: Relevance
“…The results of our model are based upon the assumptions that all birds stop at exactly three staging sites. We expect to observe the same trends in infection dynamics for any biologically realistic number of staging sites, for example, as obtained from satellite tracking studies [18], [32]. However any model which does not include staging sites, whereby birds transfer directly back and forth between breeding and wintering grounds, would fail to reproduce the predictions that we have presented here.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The results of our model are based upon the assumptions that all birds stop at exactly three staging sites. We expect to observe the same trends in infection dynamics for any biologically realistic number of staging sites, for example, as obtained from satellite tracking studies [18], [32]. However any model which does not include staging sites, whereby birds transfer directly back and forth between breeding and wintering grounds, would fail to reproduce the predictions that we have presented here.…”
Section: Discussionsupporting
confidence: 61%
“…During these migration periods, the birds rest at a handful of staging sites in order to feed and recover. A satellite telemetry study by Yamaguchi et al [18] of mallards which spend winter in Japan suggests that the mean number of staging sites is between 1.3 and 3 depending on the chosen location for breeding and that mallards stay for one to four weeks at each staging site between short travel periods of a few days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of migration routes of mallard ( Anas platryhynchos ) determined by satellite telemetry have shown that besides the northward flyway from Japan to Russia, a northwestward flyway also exists in Far East Russia. 26 In Japan, WN virus activity has not yet been detected. In the metropolitan area of Tokyo from 2002 to 2006, a total of 7,281 mosquitoes and 139 crow samples (blood, brain, kidney, and spleen) were tested for WN virus RNA, and none of them were positive.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of such relatedness is supported, as well, by the presence of our H5N2 isolate Akita/714/06 H5N2 in Japan in the same host, at the same place, 11 months earlier, considering that pintails wintering in Japan and Korea regularly congregate in their Siberian breeding grounds. This ecoepidemiologic interface may further be enhanced by mallards that seasonally move from Japan to Siberia through Korea [37]. The Japanese-Korean-Siberian phylogeographical axis seems to be, then, particularly important for ongoing generation of novel viral strains through conveyance of certain genes and genomes by migratory ducks, including such that circulate among pigs and human.…”
Section: Discussionmentioning
confidence: 99%